PERAN FOOD AND BEVERAGE DEPARTEMENT DALAM MENINGKATKAN PELAYANAN TERHADAP TAMU DI SAHID RAYA HOTEL YOGYAKARTA - , LAILA NAJMI; , Arina Pramusita M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Tourism industry such as hotels and restaurants and other catering businesses, these days are growing calls for a creation of a good atmosphere of the various aspects to be given or offered as a product to prospective customers. Hotel Sahid Raya Yogyakarta always strive to improve the quality to gain customer satisfaction. One of the efforts is to improve the quality of care in the Food and Beverage Department. The department has an important responsibility to provide and maintain the quality of food and drinks at the hotel. The purpose of this analysis was to determine the duties and responsibilities of Food and Beverage Department in the Hotel Sahid Raya Yogyakarta, knowing the efforts made to improve service to guests, knowing that in facing obstacles and how to overcome them. Method of data collection was conducted observations and interviews. Results of this analysis indicate that the role of the Food and Beverage Department plays an important role because it can generate profits because the guests staying at the hotel do not just need a bed (room), but also requires food and min Uman to be examined by the Food and Beverage Department. Good hotel in general we can value of comfort, cleanliness, and quality of service of the hotel. Good restaurants can be the value of the service or the service provided, the quality of food and taste of the food. Personal hygiene can improve the quality of service and quality of the hotel.